Respuesta :
Answer:
x = -12/14 is the required solution for the given expression.
Step-by-step explanation:
Here, the given expression is:
5 – 6 x = 8 x + 17
Now, here solving the expression for the value of x, we get:
5 – 6 x = 8 x + 17
⇒ 5 - 17 = 8 x + 6 x
⇒- 12 = 14 x
or, x = -12 / 14
Hence, x = -12/14 is the required solution for the given expression.
Answer: -6/7
Step-by-step explanation:
5 - 6x = 8x + 17
-5 -5 <= subtract 5 from both sides
-6 x = 8x + 12
-8x -8x <= subtract -8x from both sides to isolate the variable
-14x = 12
-14 -14 <= divide by -14 to factor out and isolate x
-12/14 can be simplified to -6/7